(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
John Clarke and the struggle for religious freedom. John Clarke is one of the pioneers of the Baptist faith in the New World of the seventeenth century, but also one of the most remarkable fighters for religious freedom. He has not yet received the attention he deserves for his strategic battle for achieving a place where freedom of conscience can be literally lived out. Inspired by Roger Williams of the Providence Plantation, Clarke and others purchase an island from the Indians in order to create a haven for all those wanting to freely exercise what they believe to be the right to religious freedom. John Clarke, a highly educated Englishman who had sailed to the new shores in order to find freedom, takes on the challenge of getting the approval by the English Crown of a charter that would offer religious freedom to all inhabitants of the newly formed Rhode Island colony. In 1663, the Baptist pastor receives the charter signed by the King, a constitution that was unique at the time and which was the longest surviving fundamental law of a state until the nineteenth century.